Ecology and qualitative phytochemical profiles of wild orchids in Palolo Education Forest, Central Sulawesi, Indonesia - MUHAMMAD SYAIFUDDIN NASRUN; ROSMANIAR GAILEA; ARYANDI FATAH JIHAD BUAMONA (Society for Indonesian Biodiversity, 2026)
Abstract. Nasrun MS, Gailea R, Buamona AFJ. 2026. Ecology and qualitative phytochemical profiles of wild orchids in Palolo Education Forest, Central Sulawesi, Indonesia. Biodiversitas 27 (4): d270429. https://doi.org/10.13057/biodiv/d270429. Orchid diversity, community structure, and qualitative phytochemical profiles were investigated in KHDTK-HPUM, an education forest in Palolo Sub-district, Sigi District, Central Sulawesi, Indonesia. Orchids were recorded along three transects (1,500 m x 10 m each; 4.5 ha searched corridor) across forest edge, riverside, and forest interior habitats using a searched-corridor encounter survey. A total of 15 orchid species belonging to 10 genera were recorded, comprising 91 clump-based individuals; 14 species (93.33%) were epiphytic, and one was terrestrial. Species richness index (Da) ranged from 1.44 to 3.17, and Shannon diversity index (H') from 0.66 to 1.08, indicating low to moderate diversity. Liparis latifolia (IVI = 41.76%, n = 25) and Liparis pallida (IVI = 39.56%, n = 23) were the ecologically dominant species. Appendicula celebica, an orchid endemic to Sulawesi, was also recorded (IVI = 21.32%), highlighting the biogeographic significance of the study area within the Wallacea biodiversity hotspot. Qualitative phytochemical screening of six species at Pharmacy Laboratory, Universitas Tadulako, detected alkaloids, flavonoids, saponins, tannins, steroids, and triterpenoids, with compound-class profiles varying notably between plant parts. Dendrobium crumenatum showed the most complete profile across stem and leaf tissues. An exploratory dual-criteria framework identified three species as Priority I for further cultivation-oriented research: L. latifolia and Cymbidium finlaysonianum (Priority I-A) and D. crumenatum (Priority I-B). These findings provide a first descriptive baseline of orchid ecology and qualitative phytochemical profiles for KHDTK-HPUM. All comparisons and priority rankings are preliminary and should be interpreted within the constraints of the exploratory sampling design.